A Case Report of Bardet Biedl Syndrome in a Patient from Pakistan who Presented with Osmotic Symptoms associated with Diabetes Mellitus - Bakht Babar; Muqsit Ali Shaukat; Misbah Manzoor; Samina Bibi; Hashim Khan (University Library System, University of Pittsburgh, 2024)
Background: The primary features of Bardet Biedl syndrome (BBS) are characterized by retinal degeneration, central obesity, post-axial polydactyly, intellectual impairment, hypogonadism, and renal anomalies. The secondary clinical features are syndactyly, delay in the achievement of developmental milestones, diabetes insipidus, diabetes mellitus, congenital heart disease and liver involvement. It is diagnosed when a patient has either four primary or three primary and two secondary clinical features and the management depends upon those predominant features.  Case presentation: A 12-year-old boy presented with polyuria, polydipsia and polyphagia. His developmental milestones were delayed and had syndromic features on physical exmination. Ultrasound of the abdomen and pelvis showed mild right-side hydronephrosis. His BMI was 28 and HbA1c was 18.3%, and values of LH and FSH were decreased. As a result, he was diagnosed with a case of BBS. He was commenced on insulin therapy with  Insulin Regular (Human Insulin)and Insulin NPH (Human Insulin).  Conclusion: Patients presenting with polyuria, polydipsia, polyphagia along with the presence of syndromic features, should be assessed for BBS as osmotic symptoms associated with diabetes mellitus can be initial clinical presentation of BBS. Its management depends upon the signs and symptoms of the patient. Various options including weight loss, exercise, oral hypoglycemic drugs, and insulin are available to treat diabetes mellitus in BBS. Some cases can have very high levels of HbA1c on initial presentation, which may require insulin without trying oral hypoglycemic drugs to treat diabetes mellitus in BBS.